Peita, suborno e a construção do conceito jurídico-penal de corrupção: patronato e venalidade no Brasil imperial (1824-1889) - Aléxia Alvim Machado Faria (2018)
If attributing a meaning to a name implies bringing connotations and circumstances that are only dully comprehensible when analysed historically, the choice of a name for a particularly reprehensible crime carries a sort of symbology that transcends mere occasionality or influence from other jurisdictions. And when the term is corruption a multisignificant word that until today comprises many other conducts besides the trade of functional acts , to figure when and why it starts to describe specific forms of crime is to identify the birth of a symbolism that remains strong up to the present time. This dissertation makes use of periodicals, criminal law books, legislation and parliamentary annals of Imperial Brazil, as well as foreign laws comparable to the Brazilian experience, to analyse the process by which the crimes nowadays described as passive corruption and active corruption at the time, peita and suborno are referred to as forms of corrupção, until they became the main designation of these felonies in the criminal-legal sphere. Concurrently, it examines the meanings attributed to corruption until and during the Brazilian Empire, reckoning a change in the most relevant historical concepts. The results point towards the modification of the very meaning of public good and public administration, to the emergence of crimes of responsibility in Brazil, and to the specific choice for two behaviors considered especially reprehensible in nineteenth-century Brazil: favour exchange mainly motivated by political sponsorship here called patronage and the burdensome vice of selling acts in the public office for the mere purpose of gaining more advantage often expressed at the time as venality. They also identify that three groups are treated otherwise in peita and suborno. Both crimes have different penalties for the public official in a broad sense, for the judge and for the minister of state. The emergence of the first group as outlaws seems natural since it is linked to the very special reproof of the crimes committed against the Public Administration, which is born and expands throughout the Brazilian Empire. Why magistrates received much more severe penalties than other officials and ministers have more indulgent penalties and even different descriptions of both crimes, the scrutiny of the legal and political context of the time was paramount to indicate.